ANALISIS KUALITAS PRODUK, HARGA DAN IKLAN TERHADAP KEPUTUSAN PEMBELIAN ALAT TULIS DI KOPERASI SMPN 1 BOJONEGARA - Wirtadipura, Dian (Jurnal Studia Akuntansi dan Bisnis (The Indonesian Journal of Management & Accounting), 2023)
The increase in the variety of products is driven by the attractiveness of the market which increasingly wants a variety of products, so the company offers a variety of various development products as well. This product development was carried out by the UPT SMPN 1 Bojonegara Cooperative in an effort to overcome the decline in sales. The purpose of this research is to determine the implementation of product development carried out by the company and its benefits in increasing sales volume. This research is qualitative research, with a case study approach. The data used are primary and secondary data, using interview, observation and documentation data collection techniques. The data analysis process in this research uses Miles and Hubermen's theory, namely data reduction, data presentation, and conclusions and verification. This aims to determine the challenges/constraints and benefits of implementing product development to increase sales volume. The results of the research show that the launch of two reading book products actually played a significant role in increasing sales volume. This can be seen from the strong relationship between product development carried out by the School and the addition of new products to the large number of purchases obtained.